Cardiac Ion Channel Regulation in Obesity and the Metabolic Syndrome: Relevance to Long QT Syndrome and Atrial Fibrillation - Aromolaran, Ademuyiwa S.; Boutjdir, Mohamed (Frontiers in Physiology, 2017)
Obesity and its associated metabolic dysregulation leading to metabolic syndrome is an epidemic that poses a significant public health problem. More than one-third of the world population is overweight or obese leading to enhanced risk of cardiovascular disease (CVD) incidence and mortality. Obesity predisposes to atrial fibrillation, ventricular and supraventricular arrhythmias; conditions that are underlain by dysfunction in electrical activity of the heart. To date, current therapeutic options for cardiomyopathy of obesity are limited, suggesting that there is considerable room for development of therapeutic interventions with novel mechanisms of action that will help normalize rhythm in obese patients. Emerging candidates for modulation by obesity are cardiac ion channels and Ca handling proteins. However, the underlying molecular mechanisms of the impact of obesity on these channels/Ca handling proteins remain incompletely understood. Obesity is marked by accumulation of adipose tissue associated with a variety of adverse adaptations including dyslipidemia (or abnormal levels of serum free fatty acids), increased secretion of pro-inflammatory cytokines, fibrosis, hyperglycemia and insulin resistance, that will cause electrical remodeling and thus predispose to arrhythmias. Further, adipose tissue is also associated with the accumulation of subcutaneous and visceral fat, which are marked by distinct signaling mechanisms. Thus, there may also be functional differences in the outcome of regional distribution of fat deposits on ion channel/Ca handling proteins expression. Evaluating alterations in their functional expression in obesity will lead to progress in the knowledge about the mechanisms responsible for obesity-related arrhythmias. These advances are likely to reveal new targets for pharmacological modulation. The objective of this article is to review cardiac ion channel/Ca handling proteins remodeling that predispose to arrhythmias. Understanding how obesity and related mechanisms lead to cardiac electrical remodeling is likely to have a significant medical and economic impact.